Regional Input-Output Matrices and an Application to Analyze a Manufacturing Export Shock in Mexico - Alvarado, Jorge A.; Quiroga, Miroslava; Torre, Leonardo E.; Chiquiar, Daniel I. (Ensayos Revista de Economía, 2019)
Based on the national Input-Output Matrix (IOM) 2012 calculated by INEGI, we estimate with the Flegg approach four regional Input-Output Matrices (RIOMs) using Banco de México’s regionalization (Northern, North-Central, Central and Southern). These RIOMs are employed to evaluate the impact on regional gross output, value added and employment from a 10,000 million dollar shock on Mexican manufacturing exports. The results show that the effects on the absolute values of gross output, value added and employment in the North are clearly larger than those estimated for the other regions. Another finding is that the total effects of the regional shocks tend to concentrate in the manufacturing sector, with the highest concentration observed in the North, and the lowest in the South. It is also shown that the North is, by far, the region experiencing the greatest change in its value added relative to GDP, followed by the North Central, the Central and the South. The results suggest a strong linkage between the manufacturing sector and tertiary activities, particularly commerce and services in the central regions, as well as between manufacturing and oil and gas extraction in the South. Matrices insumo producto regionales y una aplicación para analizar impactos de las exportaciones manufactureras en México RESUMEN 2012, calculada por el INEGI, estimamos cuatro Matrices de Insumo-Producto regionales (MIPRs) utilizando el enfoque de Flegg. Estas matrices se emplean para evaluar el impacto en producción bruta, valor agregado y empleo en el nivel regional de un choque de 10,000 millones de dlares, en las exportaciones manufactureras mexicanas. Los resultados muestran que los efectos sobre los valores absolutos de la producción bruta, el valor agregado y el empleo en el Norte son significativamente mayores que los estimados para las otras regiones. Se observa también que los efectos totales de los choques regionales tienden a concentrarse en el sector manufacturero, y que la mayor concentración se encuentra en el Norte, y la más baja, en el Sur. El Norte es también la región con el mayor cambio en valor agregado como proporción del PIB, seguida por la región Centro Norte, Centro y Sur. Sin embargo, los efectos indirectos tienden a ser mayores en regiones alejadas de la frontera con Estados Unidos. Así, los resultados sugieren un fuerte vínculo entre el sector manufacturero y las actividades terciarias, en particular, el comercio y los servicios en las regiones centrales, y en la fabricación y la extracción de petróleo y gas en el Sur.